2020
DOI: 10.1097/corr.0000000000001554
|View full text |Cite
|
Sign up to set email alerts
|

High Risk of Conversion to THA After Femoroacetabular Osteoplasty for Femoroacetabular Impingement in Patients Older than 40 Years

Abstract: Background Femoroacetabular impingement (FAI) is a recognized cause of hip pain and decreased quality of life and has been linked to primary idiopathic hip osteoarthritis (OA). Although the operative indications for FAI have expanded to include older patients, we do not know whether there is an increased risk of conversion to THA after femoroacetabular osteoplasty (FAO) via the mini-open approach for FAI in patients older than 40 years compared with younger patients, after controlling for other con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Long-term studies are important to assess conversion to osteoarthritis, as this is one of the most relevant concerns in FAI. In patients undergoing arthroscopy and osteochondroplasty, one out of six patients over 40 years of age opted for total hip arthroplasty at 2 years 30 . Meanwhile, the prognosis is better 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term studies are important to assess conversion to osteoarthritis, as this is one of the most relevant concerns in FAI. In patients undergoing arthroscopy and osteochondroplasty, one out of six patients over 40 years of age opted for total hip arthroplasty at 2 years 30 . Meanwhile, the prognosis is better 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, outcomes of surgery for FAI with concomitant moderate- to advanced hip OA (Tönnis Grade ≥ 2) are equivocal, with some reports suggesting poor results and high rates of conversion to THA in the literature [ 13 , 15 , 22 ]. There is also concern that performing a joint-preservation procedure in this subgroup may lead to a rapid clinical decline that would require a THA sooner [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews of the literature have reported that the presence of OA and increasing age may result in inferior outcomes compared following hip arthroscopy [4, 5]. More recent case series have also reported higher rates of early conversion to total hip arthroplasty among these patients [6]. However, contrastingly, other case series have reported significant improvements in short‐term outcomes following arthroscopy for FAI with concomitant mild to moderate OA, with a more recent randomized trial reporting superiority compared with physiotherapy alone [7, 8].…”
Section: Introductionmentioning
confidence: 99%